2008
DOI: 10.1142/s1084946708000922
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Dimensions in Transitional Economies: A Review of Relevant Literature and the Case of Kyrgyzstan

Abstract: The process of starting and surviving a new venture is always a challenge, and this is aggravated by unfavorable conditions especially prevalent in less affluent, developing, and transitional economies. This study reviews and integrates the literature on different entrepreneurial dimensions in transitional economies and provides a case analysis, Kyrgyzstan. The review of the entrepreneurial motivations dimension indicated four major motives behind starting a new venture, and an examination of the entrepreneuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
1
37
0
7
Order By: Relevance
“…Contrary to innovation-based economies, entrepreneurship in efficiency-driven economies is characterised by decreasing rates of self-employment (Acs, Desai & Hessels 2008), high levels of volatility (Pfeifer & Sarlija 2010), economic unpredictability (Ahlstrom & Bruton 2010), low entrepreneurial culture (Lee & Peterson 2000) and rampant numbers of necessity entrepreneurs who are mainly motivated by the lack of job opportunities or some other push factors (Yalcin & Kapu 2008) as well as low growth prospects and low aspirations (Capelleras et al 2010). …”
Section: H1amentioning
confidence: 99%
“…Contrary to innovation-based economies, entrepreneurship in efficiency-driven economies is characterised by decreasing rates of self-employment (Acs, Desai & Hessels 2008), high levels of volatility (Pfeifer & Sarlija 2010), economic unpredictability (Ahlstrom & Bruton 2010), low entrepreneurial culture (Lee & Peterson 2000) and rampant numbers of necessity entrepreneurs who are mainly motivated by the lack of job opportunities or some other push factors (Yalcin & Kapu 2008) as well as low growth prospects and low aspirations (Capelleras et al 2010). …”
Section: H1amentioning
confidence: 99%
“…Researchers [4,5] contend that to understand the entrepreneurial process, one must understand entrepreneurs' motivation to start and sustain their venture. Motivating factors, which can be either internal or external to the entrepreneur, classified motivators into four categories: financial rewards (extrinsic rewards), independence/autonomy, personal growth (intrinsic rewards) and family security [2,4]. Motivating factors can also be classified as push or pull factors.…”
Section: What Motivates Entrepreneurs: Literature Reviewmentioning
confidence: 99%
“…Motivating factors can also be classified as push or pull factors. 'Push factors include the need to increase family income, dissatisfaction with a salary-based job, problems with finding an appropriate job and the need for In their study of Kyrgyzstan entrepreneurs, Yalcin and Kapu found the desire to earn more money and the lack of appropriate job opportunities to be the key motivators [2]. Chu et al (2007) found that among Kenyan and Ghanaian entrepreneurs, the top motivators were increasing income, creating a job for oneself, personal satisfaction and growth, and job security.…”
Section: What Motivates Entrepreneurs: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The domestic industry (e.g. SMEs) also badly suffers for similar grounds (Amroune, Hafsi, Bernard, & Plaisent, 2014;Yalcin & Kapu, 2008). External variables are thus found exceedingly influential in shaping the business decisions and continuity of the industry.…”
Section: The Predicament and The Resolvementioning
confidence: 99%